Biased perceptions of other people's attitudes to carbon taxation. (August 2022) - Drews, Stefan; Savin, Ivan; van den Bergh, Jeroen C.J.M.
Abstract: Beliefs about other people's opinions on climate change influence one's own opinion. Such beliefs can, however, suffer from biases in perception. Using two nationally representative surveys, we examine this issue in a new context, namely of carbon-tax acceptance in Spain. We find that the more one expects the tax to be accepted by others, the more one accepts it personally. But opponents of a carbon tax tend to strongly overestimate the prevalence of their opinion, i.e. they exhibit a so-called false consensus effect. In contrast, despite holding the majority view, tax supporters somewhat underestimate the prevalence of their own view, which is known as pluralistic ignorance. We further test the role of information provision by providing participants with different percentages of people accepting the tax. Overall, we find little evidence that such information provision significantly increases tax acceptance. The impact of information provision on tax acceptance tends to be moderated by the degree of false consensus. Highlights: Carbon tax opponents believe that their opinion is more common than it actually is. Carbon tax supporters underestimate the prevalence of their own view. Undecided citizens tend to overestimate carbon tax opposition. We test the effects of information provision about others' policy opinions. People overestimating prevalence of their own opinion less are likely to revise it.